Design-driven innovation : changing the rules of competition by radically innovating what things mean. - Verganti, Roberto, ....- (Boston : Harvard, 2009)
Until now, the literature on innovation has focused either on radical innovation pushed by technology or incremental innovation pulled by the market. In Design-Driven Innovation: How to Compete by Radically Innovating the Meaning of Products, Roberto Verganti introduces a third strategy, a radical shift in perspective that introduces a bold new way of competing. Design-driven innovations do not come from the market; they create new markets. They don't push new technologies; they push new meanings. It's about having a vision, and taking that vision to your customers. Think of game-changers like Nintendo's Wii or Apple's iPod. They overturned our understanding of what a video game means and how we listen to music. Customers had not asked for these new meanings, but once they experienced them, it was love at first sight. But where does the vision come from? With fascinating examples from leading European and American companies, Verganti shows that for truly breakthrough products and services, we must look beyond customers and users to those he calls "interpreters" - the experts who deeply understand and shape the markets they work in. Design-Driven Innovation offers a provocative new view of innovation thinking and practice.